Questions to Ask Before Agreeing to Surgery - Martie Gillen; Carolyn S. Wilken (EDIS)
Before you agree to have surgery, you need to be aware of the risks and benefits. The best way to do this is to discuss the surgery with your doctor. Use this worksheet to ask questions and take notes so that you have all the information you need. This revised 3-page fact sheet was written by Martie Gillen and Carolyn S. Wilken, and published by the UF Department of Family, Youth and Community Sciences, August 2012.